1996
DOI: 10.1021/om9501945
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene, Styrene, and α-Methylstyrene Polymerization by Mono(pentamethylcyclopentadienyl) (Cp*) Complexes of Titanium, Zirconium, and Hafnium:  Roles of Cationic Complexes of the Type [Cp*MR2]+ (R = Alkyl) as both Coordination Polymerization Catalysts and Carbocationic Polymerization Initiators

Abstract: A variety of monocyclopentadienyl and mono(pentamethylcyclopentadienyl) complexes of titanium, zirconium, and hafnium are assessed for abilities to initiate polymerization of ethylene, styrene, and, in part, α-methylstyrene. In general, little or no activity was found for either neutral species of the types CpMMe3 and CpMMe2OR or for cationic 12- and 14-electron species of the types [CpMR2L]+ and [CpMR2L2]+, respectively (Cp = η5-cyclopentadienyl; R = alkyl; L = amine, phosphine ligands). In contrast, much bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
4

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(67 citation statements)
references
References 58 publications
2
61
0
4
Order By: Relevance
“…A single sharp resonance for the phenyl C-1 carbon was observed at 142.9 ppm, assignable to syndiotactic sequence. Wang et al reported that a significant amount of atactic polystyrene (extractable by fractionation with 2-butanone) was formed with a similar catalytic system at low polymerization temperatures 16) . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A single sharp resonance for the phenyl C-1 carbon was observed at 142.9 ppm, assignable to syndiotactic sequence. Wang et al reported that a significant amount of atactic polystyrene (extractable by fractionation with 2-butanone) was formed with a similar catalytic system at low polymerization temperatures 16) . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, mono( 5 -cyclopentadienyl)titanium complexes activated by MAO for syndiospecific polymerization of styrene are well known, [1][2][3][4][5] as well as for the polymerization of ethylene 6,7 and propylene. 8,9 The active species of mono( 5 -cyclopentadienyl)titanium/MAO catalyzing different monomers have been analyzed by various methods.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever the primary styrene incorporation occurs, the system proposed should bear carbocationic active sites that are responsible for the initial stage of atactic PS design. Eventually, carbocationic active sites yielding atactic PS at low polymerization temperature (0°C) were assigned by Baird et al 40 to switching properties (sPS 3 atactic product) of Cp*TiMe 3 /B(C 6 F 5 ) 3 catalyst. Shaffer and Ashbaugh 41 demonstrated that NCA (RB Ϫ (C 6 F 5 ) 3 and B Ϫ (C 6 F 5 ) 4 ) can bear active sites for carbocationic styrene polymerization in the presence of either metallocene or nonmetallocene complexes under specified conditions.…”
Section: Resultsmentioning
confidence: 99%